1985
DOI: 10.1016/0166-0934(85)90131-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the susceptibility of three human gut tumour-derived differentiated epithelial cell lines, primary monkey kidney cells and human rhabdomyosarcoma cell line to 66-prototype strains of human enteroviruses

Abstract: The growth of prototype strains of 31 serotypes of ECHO, 3 polio, 6 Coxsackie B, 24 Coxsackie A and enterovirus serotypes 70 and 71 were tested in parallel in primary monkey kidney cells (PMK), RD cells and three gut tumour-derived differentiated epithelial cell lines (HRT-18 HT-29 in SKCO-1). All 31 serotypes of ECHO viruses grew in HT-29, 27 and SKCO-1, 5 in HRT-18, 29 in PMK and 29 in RD. There was good growth of poliovirus serotypes in all five cell types. Coxsackie B viruses grew well in all the cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
5
4
0
Order By: Relevance
“…These findings agree with data from previous studies for isolation of group B coxsackieviruses (Menegus and Hollick, 1982;Patel et al, 1985;Dagan and Menegus, 1986;Dahling and Wright, 1986;Chonmaitree et al, 1988;Huang et al, 2002). While isolation of coxsackievirus group A serotypes from cell culture is difficult (Schmidt et al, 1975;Lipson et al, 1988), we recovered most of coxsackievirus A9 serotype from PMK cells.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…These findings agree with data from previous studies for isolation of group B coxsackieviruses (Menegus and Hollick, 1982;Patel et al, 1985;Dagan and Menegus, 1986;Dahling and Wright, 1986;Chonmaitree et al, 1988;Huang et al, 2002). While isolation of coxsackievirus group A serotypes from cell culture is difficult (Schmidt et al, 1975;Lipson et al, 1988), we recovered most of coxsackievirus A9 serotype from PMK cells.…”
Section: Discussionsupporting
confidence: 95%
“…Echovirus replication was adequately supported by RD cells in the present study, and previous reports corroborate these findings (Patel et al, 1985;Lipson et al, 1988;Kok et al, 1998;Wang et al, 2002;Perez-Ruiz et al, 2003). Without RD cells we would have failed to detect 10% of echovirus 30 isolates, the most common enterovirus isolated during 2004 (CDC, 2004).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in agreement with a previous study of Patel et al [22] demonstrating that two gut tumour-derived cell lines, HT-29 and SKCO-1, have a markedly wider susceptibility with comparable or wider sensitivity for enteroviruses than primary monkey kidney cells (PMK) and rhabdomyosarcoma cells (RD).…”
Section: Discussionsupporting
confidence: 95%
“…Other cell lines, derived from intestinal tissue, have been investigated for their ability to support the growth of enteric viruses. Most of these studies have been directed at growing the more fastidious agents like rotaviruses and astroviruses, but Patel et al . (1985) carried out a large survey on the susceptibility of a range of lines to different enteroviruses, including all 31 serotypes of echovirus; they found that two lines, HT‐29 and SKCO‐1 derived from human colonic carcinoma, had a markedly wider sensitivity for enteroviruses than primary monkey kidney or RD cell cultures.…”
Section: Detection Enumeration and Identificationmentioning
confidence: 99%